Penerapan Lean Manufacturing untuk Meminimasi Waste pada Produksi Udang Beku - Saraswati, Ni Nyoman Ayu; Syafnijal, Frieska Ariesta (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The Factory faces the significant challenge of managing waste to improve productivity and reduce operational costs. This study specifically addresses waste generated during the production of frozen shrimp, a high-value Indonesian fishery commodity. This paper is aim to analyze and minimize the waste using the Lean Manufacturing. The Lean Manufacturing was executed through three key steps: Current State Value Stream Mapping (VSM), Classification of production activities, and Identification and analysis of specific wastes.The results indicate that implementing the prescribed Lean manufacturing methods can significantly address the company's waste issues, leading to both increased productivity and a substantial reduction in costly waste expenses. The implementation at PT XYZ was based on aligning theoretical Lean concepts with empirical field data, which is intended to serve as a valuable alternative learning resource for future development.